Teacher in Quran Discourse: Formation of Quranic Mind at SMA 33 Negeri Jakarta - farida, Laila; Purwidianto (Universitas Muhammadiyah Prof Dr Hamka, 2023)
This research was motivated by some students at SMA Negeri 33 Jakarta who experienced difficulties in reading the Al-Quran and lacked understanding of the science of tajwid, so this research aims to determine the role of Islamic Religious Education and Character teachers in improving high school students' Al-Quran reading skills. 33 Jakarta. This research is a qualitative research. The data collection techniques used were observation of Islamic Religious Education and Characteristics subjects, interviews of Islamic Religious Education teachers at SMA Negeri 33 Jakarta and students in class X-5 and documentation. The results of the research show that the role of Islamic Religious Education and Character Teachers at SMA Negeri 33 Jakarta in improving students' ability to read the Al-Quran is: (1) The teacher teaches how to read the Al-Quran correctly. (2) Additional hours of Al-Quran learning outside of Teaching and Learning Activities. (3) Islamic Religious Education Teachers facilitate teaching materials such as Iqro and Juz Amma. (4) The teacher corrects the students' incorrect reading of the Koran. (5) The teacher introduces the science of recitation and waqf signs. (6) The teacher repeats Al-Quran material. (7) Teachers use Al-Quran learning methods, namely the peer method and memorization method. Thus, the role of Islamic Religious Education and Character Education teachers in improving students' Al-Quran reading skills includes teachers as teachers, mentors and facilitators.